2021
DOI: 10.3390/antiox10070996
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic Parameters Show Specific Responses to Essential Mineral Deficiencies

Abstract: In response to decreases in the assimilation efficiency of CO2, plants oxidize the reaction center chlorophyll (P700) of photosystem I (PSI) to suppress reactive oxygen species (ROS) production. In hydro-cultured sunflower leaves experiencing essential mineral deficiencies, we analyzed the following parameters that characterize PSI and PSII: (1) the reduction-oxidation states of P700 [Y(I), Y(NA), and Y(ND)]; (2) the relative electron flux in PSII [Y(II)]; (3) the reduction state of the primary electron accept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 97 publications
0
17
0
1
Order By: Relevance
“…Although Zn enrichment occurs when its contents exceed the level of sufficiency within a crop plant, oversupply can have negative metabolic and structural consequences at cellular and tissue levels [ 33 ]. Indeed, a deficiency or excess of Zn can negatively affect water tensions, creating ionic unbalance, and inhibit many physiological processes, namely, the synthesis of protein and carbohydrates, auxin biosynthesis, cellular division, membrane structural integrity, photosynthesis and seed germination, due to its role as a cofactor for many enzymes [ 33 , 34 ]. Besides, protein-binding Zn also is central in a plant’s metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Although Zn enrichment occurs when its contents exceed the level of sufficiency within a crop plant, oversupply can have negative metabolic and structural consequences at cellular and tissue levels [ 33 ]. Indeed, a deficiency or excess of Zn can negatively affect water tensions, creating ionic unbalance, and inhibit many physiological processes, namely, the synthesis of protein and carbohydrates, auxin biosynthesis, cellular division, membrane structural integrity, photosynthesis and seed germination, due to its role as a cofactor for many enzymes [ 33 , 34 ]. Besides, protein-binding Zn also is central in a plant’s metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…There are few studies on the physiological effects of copper deficiency on vascular plants, but also in plants plastocyanin would be a potential target. Ohnishi et al (2021) indeed observed on the basis of DUAL-KLAS-NIR measurements, allowing the quantification of the PC signal, that Cu-deficient plants have a much lower PC/P700 ratio. Another potential target is the Cu/Zn superoxide dismutase (SOD; Tainer et al, 1983 ; Bowler et al, 1992 ).…”
Section: What Does the Literature Tell Us About These Mineral Deficie...mentioning
confidence: 82%
“…Since the introduction of instruments for the measurement of Chl fluorescence and NIR kinetics (820 nm single channel measurements, P700 measurements derived from the difference between 830 and 870 nm, and deconvolution of PC, P700, and Fd signals on the basis of the measurement of 4 NIR wavelength pairs), it is possible to study the kinetics of photosystem (PS) II and PS I in detail. In a recent study, Ohnishi et al (2021) characterized twelve mineral deficiencies on the basis of the kinetics of the operational quantum yield of PS II: Y(II), operational quantum yield of PS I: Y(I), yield of PS I donor side limitations: Y(ND), and yield of PS I acceptor side limitations: Y(NA) measured during 10 min of illumination, using a DUAL-PAM-100. This approach gives information on the impact of these 12 deficiencies on photosynthetic activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The robustness of ascorbate recycling would be required for plant acclimation to such harsh conditions, in which ROS production and subsequent ascorbate oxidation and degradation are highly enhanced. Also, a very recent work has demonstrated that photosystem I is severely damaged under deficiencies of some nutrients [ 71 ], leading to enhanced ROS production in chloroplasts. It will be fascinating to study the role of ascorbate recycling enzymes under such harsh conditions in future work.…”
Section: Discussionmentioning
confidence: 99%